Eduards Pētersons - pirmais pedagoģijas doktors Latvijā - Puķīte, Santa (LU Muzejs, 2024)
Raksts par pirmo pedagoģijas doktoru Latvijā, Latvijas Universitātes (LU) docentu un ārštata ārkārtas profesoru, Triju zvaigžņu ordeņa virsnieku Eduardu Pētersonu. Raksts tapis kā papildinājums LU Muzeja mēneša priekšmeta rakstam - Pirmā disertācija pedagoģijā Latvijā.
An article about Latvia's first doctor of pedagogy, docent and freelance extraordinary professor of the University of Latvia (UL), an officer of the Order of the Three Stars Eduards Pētersons. The article was written as an addition to the monthly object of the UL Museum - First Dissertation in Pedagogy in Latvia.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Pedagoģija; Audzināšana; Izglītība; Pedagogy; Education